2021
DOI: 10.1016/j.pedhc.2021.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Intentions to Vaccinate Their Children Against COVID-19

Abstract: Introduction With the COVID-19 vaccine rollout is well underway now beginning in children ages 12 and over, it is unknown what percent of parents plan to vaccinate their children against COVID-19. Method The purpose of this descriptive correlational study was to examine parents’ attitudes, beliefs, and behaviors in administering a COVID-19 vaccine. Results Only 21.93% of the subjects reported overall VH. Half of parents (49.45%) say they want… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
106
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 9 publications
12
106
1
1
Order By: Relevance
“…Regarding the factors that influence parents’ intention to vaccinate their children, we found that parents who had a higher level of knowledge and fewer concerns about COVID-19 vaccines were more likely to vaccinate their children. This finding is confirmed by the literature since confidence in COVID-19 vaccine safety and effectiveness is one of the strongest predictors of vaccine acceptance (Ruggiero et al, 2021; Skjefte et al, 2021; Yilmaz and Sahin, 2021; Zhang et al, 2020). Moreover, confidence in COVID-19 vaccine safety and effectiveness shows a great variation among countries affecting vaccine acceptance (Skjefte et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Regarding the factors that influence parents’ intention to vaccinate their children, we found that parents who had a higher level of knowledge and fewer concerns about COVID-19 vaccines were more likely to vaccinate their children. This finding is confirmed by the literature since confidence in COVID-19 vaccine safety and effectiveness is one of the strongest predictors of vaccine acceptance (Ruggiero et al, 2021; Skjefte et al, 2021; Yilmaz and Sahin, 2021; Zhang et al, 2020). Moreover, confidence in COVID-19 vaccine safety and effectiveness shows a great variation among countries affecting vaccine acceptance (Skjefte et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…An important parental willingness of vaccination in our study was positive influenza vaccination history in the last season. This finding echoes the results of research which show that COVID-19 vaccine acceptance is higher both among parents who are vaccinated for influenza (Goldman et al, 2020; Kelly et al, 2021) and among parents who vaccinate their children for influenza (Ruggiero et al, 2021). Influenza vaccination shows parents’ positive attitude towards vaccination, which is extremely important as there is a positive relationship between past and future behavior (Ouellette and Wood, 1998).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Those findings are in contrast to a widening gap in attitudes between fathers and mothers found in the U.S. where a quarter of mothers said they are “extremely unlikely” to vaccinate their children [ 29 ]. If concerns about safety of the vaccine [ 24 ] affect caregiver decision making, potential association of one COVID-19 vaccine to myocarditis in adolescents [ 30 ] may have further broadened this gap and public health organizations should find channels of communication directly to alleviate concerns expressed by caregivers. These may include advertising on social media channels to subgroups of the population, or through particular school systems in regions with a known high rate of vaccine hesitancy.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine hesitancy (9.9%) was higher among caregivers who were mothers of children aged 6-10 years, younger than 29 years old, had lower educational level, relied on information found on the web/social media, and disliked mandatory vaccination policies [23]. In a recent online survey in the U.S. with 427 participants, 44% planned to vaccinate children against COVID-19 once the vaccine becomes available to them [24], reflecting similar findings as in our cohort after the vaccine was approved in adults. However, 75% of children were reported to have chronic conditions, a much higher rate than in the general population, or the cohort of families completing our international study.…”
Section: Discussionmentioning
confidence: 99%